Pendidikan Kesehatan Melalui Whatsapp Group Meningkatkan Pengetahuan dan Sikap Karang Taruna dalam Menghadapi Bencana Tsunami di Pesisir Pantai Tanah Lot - Kadek Mahendra Prasetia Adinata; I Wayan Sukawana; I Gusti Ayu Ari Rasdini; I Made Sukarja; Ni Made Juniari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2021)
The island of Bali is located very close to the subduction zone of the Indo-Australian plate and the Eurasian plate which often triggers large earthquakes and even predicted to cause a tsunami. A tsunami is a series of water caused by a large displacement of water in the sea which then becomes a series of powerful destructive waves when it arrives at the beach. The BNPB survey found that people's knowledge and attitudes were very lack in dealing with the tsunami disaster. The purpose of this study was to determine the effect of health education through WhatsApp groups on the knowledge and attitudes of youth groups in dealing with the tsunami disaster on the Tanah Lot coast. Pre-experimental research was conducted on 39 members of the youth organization in Beraban Village, Kediri District, Tabanan. Health education is carried out by giving modules, lectures using the zoom application and discussions via WhatsApp groups for 1 week in the first week of May 2021. Pre and post data are collected via google form. Male respondents were 51.3% and 92.3% of respondents were 18 years old. There was an increase of 77.98% in the score and significant in the paired t-test (sig. value = 0.001) on the level of knowledge and attitudes of youth organizations in dealing with tsunami disaster on the Tanah Lot coast after being given health education via WhatsApp group for one month. After this research, hoped that the youth leaders will continue to update information through WhatsApp groups so that they have good knowledge and attitudes in dealing with the tsunami disaster.